Phosphoenolpyruvate regulates the Th17 transcriptional program and inhibits autoimmunity - Tsung-Yen Huang; Masato Hirota; Daiki Sasaki; Rajkumar Singh Kalra; Hsiao-Chiao Chien; Miho Tamai; Shukla Sarkar; Yang Mi; Mio Miyagi; Yu Seto; Hiroki Ishikawa (Cell Reports, 2023)
Summary: Aerobic glycolysis, a metabolic pathway essential for effector T cell survival and proliferation, regulates differentiation of autoimmune T helper (Th) 17 cells, but the mechanism underlying this regulation is largely unknown. Here, we identify a glycolytic intermediate metabolite, phosphoenolpyruvate (PEP), as a negative regulator of Th17 differentiation. PEP supplementation or inhibition of downstream glycolytic enzymes in differentiating Th17 cells increases intracellular PEP levels and inhibits interleukin (IL)-17A expression. PEP supplementation inhibits expression of signature molecules for Th17 and Th2 cells but does not significantly affect glycolysis, cell proliferation, or survival of T helper cells. Mechanistically, PEP binds to JunB and inhibits DNA binding of the JunB/basic leucine zipper transcription factor ATF-like (BATF)/interferon regulatory factor 4 (IRF4) complex, thereby modulating the Th17 transcriptional program. Furthermore, daily administration of PEP to mice inhibits generation of Th17 cells and ameliorates Th17-dependent autoimmune encephalomyelitis. These data demonstrate that PEP links aerobic glycolysis to the Th17 transcriptional program, suggesting the therapeutic potential of PEP for autoimmune diseases.